The Effects of Imitative Vs. Cognitive Methods on The Speech Development of Children With Autism - JALILI*, Monireh; Nader JAHANGIRI, Nader; YAZDI, Amir Amin; ASHRAFZADEH, Farah (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Jalili M, Jahangiri N, Yazdi Aa, Ashrafzadeh F. The Effects of Imitative Vs. Cognitive Methods on The Speech Development of Children With Autism. Iran J Child Neurol. 2014 Winter; 8(1):37-46. Objective The present study was performed to examine the effects of two speech therapy methods on six verbal behaviors of autistic children, including oral speech, listening, organizing, speaking, semantics, and syntax. Materials & Methods In this study, thirty 6-8 years old children with autism were assigned to one of two groups: imitative and cognitive groups. Before starting the main procedures of the study, the children of both groups were homogenized concerning their autism level. In the first phase of the study, the speech development level of the two groups was measured in a pre-test, in which both groups showed similar results. Then, both groups of children received 6 months of speech therapy instruction, during which one group was taught using an imitative method, while the other group was being worked with cognitive method. Results After 6-month treatment period, a post-test was done, and the t-tests based on the data of the two groups revealed a significant difference between the results. Conclusion The statistics showed that after the teaching period, autistic that worked with cognitive method gained a better development in their speech abilities, comparing to those worked with the imitative method. Reference: Samadi SA, Mahmoodizadeh A, McConkey R. A national study of the prevalence of Autism among five year old children in Iran. Autism 2012;16(1):5-14. Fombonne E, Simmons H, Ford T, Meltzer H, Goodman R. Prevalence of pervasive developmental disorders in the British nationwide survey of child mental health. J Am Acad Child Adolesc Psychiatry 2001;40(7):820-7. Fombonne, E. The changing epidemiology of Autism. J Appl Res Intellect Disabil 2005,18(4):281-94. Filipek PA, Accardo PJ, Ashwal S, Baranek GT, Cook EH Jr, Dawson G, et al. Practice parameter: screening and diagnosis of autism: report of the Quality Standards Subcommittee of the American Academy of Neurology and the Child Neurology Society. Neurology 2000;55(4):468-79. Samadi, SA. Comparative policy brief: status of intellectual disabilities in the Islamic republic of Iran. J Policy Pract Intellect Disabil 2008;5:129-32. Rogers SJ, An examination of the imitation deficit in autism. In: Nadel J, Butterworth G, editors. Imitation in infancy. Cambridge: Cambridge University Press; 1999. p.254-83. Ozonoff S, Pennington BF, Rogers SJ. Executive function deficits in high-functioning autistic individuals: Relationship to theory of mind. J Child Psychol Psychiatry 1991;32(7):1081-105. Williams JH, Whiten A, Suddendorf T, Perrett DI. Imitation, mirror neurons and autism. Neurosci Biobehav Rev 2001;25(4):287-95. Rogers SJ, Hepburn SL, Stackhouse T, Wehner E. Imitation performance in toddlers with autism and those with other developmental disorders. J Child Psychol Psychiatry 2003;44(5):763-81. Gena A, Krantz PJ, McClannahan LE, Poulson CL. Training and generalization of affective behavior displayed by youth with autism. J Appl Behav Anal 1996;29(3):291-304. Ingenmey R, Van Houten R. Using time delay to promote spontaneous speech in an autistic child. J Appl Behav Anal 1991;24(3):591-6. Ayzenson J. Language and speech disorders in children. Tehran: Roshd publications; 2010. De Giacomo A, Fombonne E. Parental recognition of developmental abnormalities in autism. Eur Child Adolesc Psychiatry 1998;7(3):131-6. Hodgdon LA. Solving behavior problems in autism: improving communication with visual strategies. Quirkroberts publishing; 2001. P.32. Bertrand J, Mars A, Boyle C, Bove F, Yeargin-Allsopp M, Decoufle P. Prevalence of autism in a United States population: the Brick Township, New Jersey, investigation. Pediatrics 2001;108(5):1155-61. Siegel B. Helping children with autism learn: a guide to treatment approaches for parents and professionals. Oxford: Oxford Press Inc; 2002. P.3. Plimley L, Bowen M. Social skills and autism spectrum disorders, London: Paul Chapman publishing; 2007. Mohammadi M, Mesgarpour B, Sahimi Izadian E, Mohammadi M. Psychiatric tests for children and young adults: CARS test. Tehran: Teimourzadeh publications; 2006. Schopler E, Mesibov GB. Diagnosis and Assessment in Autism. New York, NY: Springer publications; 1988. P.3-4. Newcomer P, Hammill D. TOLD: test of language development. (Adaption and standardization to Persian language by Hassanzadeh S and Minaei A.). Tehran: Publications of Ministry of Education; 1977. Dequinzio JA. Generalized Imitation of Facial Models by Children with Autism. J Appl Behav Anal 2007;40(4):755-9. Hatch E. Farhady H. Research design and statistics for applied linguistics. Rahnama publications; 2007. P.28. Brown JS, Rodgers T. Doing second language research. Oxford: Oxford University Press; 2004. P.47. Brown J. Understanding research in second language learning. A teacher’s guide to statistics and research design. Cambridge: Cambridge university press; 1995. P.31.